Experiencing and Understanding AIDS in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
C Becker, JP Dozon, C Obbo, and M Touré. CODESRIA. 1999.712 pp.ISBN 2 86537 945 0.FF280 Euro 42.70CODESRIA,BP 3304, Dakar, Senegal.Fax: + 221 824 1289Email: codesria@telecomplus.sn